Mathematical model of livestock and wildlife: Predation and competition under environmental disturbances - Laguna, Maria Fabiana (2015)
Fil: Laguna, Maria Fabiana. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina